Synthesis and Vaccine Evaluation of the Tumor Associated Carbohydrate Antigen RM2 from Prostate Cancer - Chuang, Hong-Yang (Springer, 2015)
This thesis focuses on the synthesis and vaccine evaluation of the prostate tumor- associated carbohydrate antigen RM2. The author first presents the use of the [1+2+3] one-pot sequential strategy to successfully synthesise the RM2 antigen and its analogues as single stereoisomers in every glycosylation step, producing good yields and stereoselectivity. He then introduces the conjugation of the synthetic RM2 antigen to the carrier protein CRM197 in an average number of 1–10 to create the prostate cancer vaccine candidate, which is combined with α-galactosylceramide C1, its analogue C34, or Alu.